INDIVIDUALIZATION OF LEARNING AS PEDAGOGICAL THE PROBLEM IN THE CONTEXT IS PERSONAL FOCUSED EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the history of individual approach in training and present-day state of given problem.